О СОХРАНЕНИИ ДИКОЙ ЯБЛОНИ И АБРИКОСА НА ТЕРРИТОРИИ ИЛЕ-АЛАТАУСКОГО ГНПП (Eurasian Journal of Ecology, 2016)
Results of research by distribution, ecology and condition of apple tree and apricot woods with dominated rare species, which listed in Red Data Book of Kazakstan - Malus sieversii (Ledeb.) M. Roem. and Armeniaca vulgaris Lam. on the territory of the Ile-Alatau national natural. Park have been generalized in this article. The authors give information about the rich distribution offorms of mentioned species, about selected and patented variety-clones, about the genetic reservations of these breeds, which have been sorted out at the territory of Park. The authors emphasize the need for special protection of unique plant communities and bring a summary of the researches on the monitoringgrounds.